Diversity and abundance of water birds in the mangrove area of south coast of Bangkalan, Madura Island, Indonesia - Ajeng Ramadhani; Reni Ambarwati; Ragil Satriyo Gumilang (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ramadhani A, Ambarwati R, Gumilang RS. 2022. Diversity and abundance of water birds in the mangrove area of south coast of Bangkalan, Madura Island, Indonesia. Biodiversitas 23: 3277-3284. The southern coastal mangrove area of ??Bangkalan, Madura Island, Indonesia, is an important bird habitat, especially for water birds. This study aimed to analyze the diversity and abundance of water birds in the southern coastal mangrove area of ??Bangkalan, Indonesia, as well as the environmental carrying capacity of this area as their habitat. Sampling was carried out using a birdwatching approach at four research stations. The diversity of water birds was analyzed using the Shannon-Wiener diversity index, while the abundance of water birds was calculated based on the abundance index. Environmental carrying capacity was analyzed descriptive-quantitatively based on the habitat profile. The results indicated that there were 15 species of water birds in the mangrove area belonging to five families in four orders, namely Charadriiformes, Ciconiiformes, Pelecaniformes, and Suliformes, with a diversity index of 1.547. There were three abundant species of water birds, namely the little egret (Egretta garzetta), Javan Pond-heron (Ardeola speciosa), and Great Egret (Ardea alba). In addition to water birds, there were nine species of arboreal birds in this area. The areas with dense mangroves provide better habitat carrying capacity for water birds compared to other coastal areas.